IMPLEMENTASI SISTEM PENATAAN ARSIP DI MADRASAH ALIYAH NEGERI 1 PEKANBARU - Karno Arianto (Indonesian Journal of Islamic Educational Management, 2018)
The aim of this study is to investigate the archives management in Madrasah Aliyah Negeri 1 Pekanbaru and to identify its obstacle and supporting factors. The participants of this research were administrator and the vice headmaster. Techniques of collecting data were interviewed, observation and documentation. Analysis of the data used Miles and Huberman model, namely data reduction, data model, and verification of conclusions. This research revealed that: this school has implemented the archives storage using the subject filling system, there was no recorded system for borrowing archives, the staffs has checked the borrowed and returned archives, the finding of the archives used manual system, this school has conducted the maintenance and security of records, the staffs has removed the archives periodically. The obstacle factors were the educational background of head of administration staffs was D3 (Diploma Degree) of Secretary in Bunda Persada Academy, and administration staffs were high school graduate. Supporting factors were infrastructures were sufficient, there was supervision by the headmaster and there was good communication and cooperation between the headmaster and administration staff.